Toxicity test of LC-50 (Lethal Concentration) surfactant LAS (Linear Alkylbenzene Sulfonate) against white snapper (Lates calcarifer) fingerlings on a laboratory scale - Daulay, Anggi Mayulina; Erniati, Erniati; ˜Akla, Cut Meurah Nurul; Erlangga, Erlangga; Imamshadiqin, Imamshadiqin (Universitas Malikussaleh, 2022)
LAS (Linear Alkylbenzene Sulfonate) surfactants are the main cleaning agents from the anionic group found in detergents that are widely used in Indonesia. LAS decomposes in surface water for 1-2 days, in sediments it decomposes for 1-3 days, in marine and estuarine systems it decomposes for 5-10 days. LAS is generally degraded by as much as 90% within 3 months, with a time ranging from 5-30 days (World Health Organization, 1996). LAS surfactants can cause damage to the gill epithelium and blockage of branchiola channels in fish. This study aims to determine the toxic effect of LAS surfactant on the survival of white snapper (Lates calcarifer) fry and to determine the toxicity value of LC50 (Lethal Concentration) of LAS surfactant to white snapper (Lates calcarifer) fry on a laboratory scale. This research was carried out on September 21 - October 04, 2021 at the Marine Science Laboratory, Faculty of Agriculture, Malikussaleh University using laboratory experimental methods with 5 treatments, namely: control treatment A (0 ppm), B (0.83 ppm), C (1.58 ppm). ), D (2.16 ppm), and E (2.91 ppm). The results of this study cause barramundi to experience irregular movements, mouth opening and operculum tend to be fast and irregular, scales are pale and peeling, and cause death, LAS surfactants affect water quality such as pH and dissolved oxygen, but have no effect on salinity and temperature. The 24-hour LC50 value is 1.95 ppm, the 48-hour LC50 value is 1.86 ppm, the 72-hour LC50 value is 1.70 ppm, and the 96-hour LC50 value is 1.58 ppm.Key words: LAS surfactant; LC50; toxicity; white snapper